To Be and How Not To Be: The Challenges Of Nation-Building in Nigeria - Adewunmi J. Falode (ARISTO, 2019)
The work is the analysis of both the various nation-building challenges that have confronted Nigeria since independence and the possible ways the country can overcome them. The dream of Nigeria since independence in 1960 is to turn itself into a viable and cohesive nation. This has become an impossible dream however due to a myriad of challenges. Nigeria is a multi-ethnic society with over 250 ethnic groups. Each of these ethnic groups also have religious and economic issues that separates them from one another.  Nigeria’s diversity has been a major obstacle in its drive to become a global and responsible player in the international community. By using the qualitative research methodology, the work identified various challenges, such as corruption, autarky, governance and distribution that have been the major barriers to the creation of a viable polity. The style used in the study is also historical, descriptive and analytical. Crucially, the study also used the concept of nation-building as its Theoretical Framework. This has made it possible for the work to highlight and posit specific pragmatic and logical ways Nigeria can overcome its nation-building challenges and emerge a viable, cohesive and functional polity in the 21st century.